Self-Induced Traumatic Macroglossia: Case Report and Literature Review - Abdullah A. Alarfaj; Ali R. AlHayek; Rashid Alghanim; Nasser A. Al-Jazan (Case Reports in Otolaryngology)
Traumatic macroglossia is an extremely rare condition characterized by a sudden edematous swelling of the tongue due to trauma. We report a rare case of traumatic macroglossia in a 37-year-old male with known trisomy 21 and epilepsy who presented to the emergency room with a huge protruded tongue due to aggressive behavior and a history of multiple tongue tractions, leading to sudden severe tongue swelling without any respiratory distress symptoms. The examination was unremarkable; fixable nasolaryngoscopy relieved bilateral vocal cord movement, and there was no laryngeal edema. The patient was managed immediately by endotracheal intubation to secure the airway, and corticosteroids were used to diminish and stop the tongue swelling. We describe the clinical management for such patients, highlighting the different causes of traumatic macroglossia. A few cases have been reported in the literature, but this is the first case to report self-induced traumatic macroglossia in a seizure-free patient managed successfully by endotracheal intubation, corticosteroids, a bite block, and warm wet dressing.